Inhibition of autophagy initiation potentiates chemosensitivity in mesothelioma. Issue 3 (14th November 2017) - Follo, Carlo; Cheng, Yao; Richards, William G.; Bueno, Raphael; Broaddus, Virginia Courtney
Abstract : The benefits of inhibiting autophagy in cancer are still controversial, with differences in outcome based on the type of tumor, the context and the particular stage of inhibition. Here, we investigated the impact of inhibiting autophagy at different stages on chemosensitivity using 3‐dimensional (3D) models of mesothelioma, including ex vivo human tumor fragment spheroids. As shown by LC3B accumulation, we successfully inhibited autophagy using either an early stage ULK1/2 inhibitor (MRT 68921) or a late stage inhibitor (hydroxychloroquine). We found that inhibition of autophagy at the early stage, but not at late stage, potentiated chemosensitivity. This effect was seen only in those spheroids with high autophagy and active initiation at steady state. Inhibition of autophagy alone, at either early or late stage, did not cause cell death, showing that the inhibitors were non‐toxic and that mesothelioma did not depend on autophagy at baseline, at least over 24 h. Using ATG13 puncta analysis, we found that autophagy initiation identified tumors that are more chemosensitive at baseline and after autophagy inhibition. Our results highlight a potential role of autophagy initiation in supporting mesothelioma cells during chemotherapy. Our work also highlights the importance of testing the inhibition of different stages in order to uncover the role of autophagy and the potential of its modulation in the treatment of cancer.